Effect of Nocturnal Oxygen Therapy on Electrocardiographic Changes Among Patients with Congestive Heart Failure - Mehdi Pishgahi; Rama Bozorgmehr; Masoud Rastgari; Mohammad Amin Abbasi (International Journal of Cardiovascular Practice, 2016)
Introduction: Nocturnal hypoxia is an important factor in increasing the risk of mortality in patients with chronic heart failure and is associated with atrial and ventricular arrhythmias. In addition, QT dispersion (QTd) is used as a prognostic sign in determining future malignant arrhythmias and sudden cardiac death. In the current study, we investigated the effect of nocturnal oxygen therapy (NOT) on electrocardiographic changes among patients with chronic heart failure.Methods: In this study, a consecutive of 154 patients (87 males and 67 females) known with chronic heart failure (EF ≤ 40%) were enrolled. The patients were administered NOT (oxygen flow of 2 L/min for 8 hours during sleeping). Electrocardiography was takenbefore and after the NOT, and RR interval, PR interval and QTd were measured each time.Results: The mean age of the participants was 61.3 ± 11.4 years. Our results revealed significant reduction in QTd (55.8 ± 7.5 vs. 61.4± 9.1 msec, P = 0.001) and heart rate (79.6 ± 4.7 vs. 76.8 ± 4.3, P = 0.001) in a patient’s electrocardiogram after NOT.Conclusions: In this study, NOT decreased heart rate and QTd in patients with chronic heart failure, but not PR interval, which could consequently decrease the risk of malignant arrhythmias and sudden cardiac death.